Brain Iron Deposits in Thalamus Is an Independent Factor for Depressive Symptoms Based on Quantitative Susceptibility Mapping in an Older Adults Community Population - Zhang, Wenhua; Zhou, Ying; Li, Qingqing; Xu, Jinjin; Yan, Shenqiang; Cai, Jinsong; Jiaerken, Yeerfan; Lou, Min (Frontiers in Psychiatry, 2019)
Objectives: With the trend of aging population, increasing prevalence of late-life depression has been identified. Several studies demonstrated that iron deposition was significantly related to the severity of symptoms in patients with depression. However, whether brain iron deposits influence depressive symptoms is so far unclear in community older adults. We measured iron deposition in deep intracranial nucleus by quantitative susceptibility mapping (QSM) and aimed to explore the relationship between iron deposition and depressive symptoms. Methods: We reviewed the data of a community population from CIRCLE study, which is a single-center prospective observational study that enrolled individuals above 40 years old with cerebral small vessel disease (SVD), while free of known dementia or stroke. We evaluated regional iron deposits on QSM, measured the volume of white matter hyperintensities (WMHs) on T2 fluid-attenuated inversion recovery, and assessed depressive symptoms by Hamilton depression scale (HDRS). We defined depressive symptom as HDRS > 7. Results: A total of 185 participants were enrolled. Participants in depressive symptom group had higher QSM value in thalamus than control group (18.79 ± 14.94 vs 13.29 ± 7.64，p=0.003). The QSM value in thalamus was an independent factor for the presence of depressive symptoms (OR=1.055; 95% CI: 1.011-1.100; p=0.013). The regional QSM values in other areas were not associated with HDRS score (all p > 0.05). No significant correlations were observed between WMHs volume and HDRS score (p > 0.05), or regional QSM values and WMHs volume (all p > 0.05). Conclusions: Our study demonstrated that iron deposits in thalamus were related to the depressive symptoms in older adults.